OPERATING SURPLUS OF LGUS IN THE CONTEXT OF LEGAL CHANGES RESULTING IN A DECLINE OF LGUS' CURRENT INCOME FROM PIT - Iwona Kowalska (Polityki Europejskie, Finanse i Marketing)
The issue of an operating surplus of local government units (LGUs) is gaining significance due to, inter alia, the enactment of legal changes resulting in a decline in the current income of LGUs from PIT. The purpose of the research is evaluation of the development of the LGUs' operating surplus in the context of legal changes (enacted in 2019-2022) causing the said decline as well as the evaluation of the mechanisms compensating LGUs for that decline. The following were applied to accomplish the research objective:(1) quantitative analysis, taking into consideration the data of the Ministry of Finance presented in the reports on LGUs' budget implementation for 2020-2021 and multi-annual financial forecasts for the LGUs’ budget plan for 2022; (2) review of source literature and legislation related to the research subject. The analysis performed for the years 2020-2022 shows that the period of growth in the value of the operating surplus in all types of LGUs in 2021 in comparison to 2020 is followed by a significant decline in its value in 2022 (as planned). Across Poland, this applies to: municipalities, cities with county rights and voivodeships. Whereas, in the case of counties (on a Poland-wide scale), no operating surplus has been planned at all for 2022. The above situation may result not only in a decline in the capacity to finance investments from the operating surplus in LGUs, but also in the differentiation of these capacities within specific LGU types. Increased differentiation of this phenomenon in specific local governments may be affected by, inter alia, the adopted system of criteria of distribution of funds as part of the compensation for the decline in current income from PIT (especially in the development part of the general subsidy).